Neutrophils isolated from systemic lupus erythematosus patients exhibit a distinct functional phenotype - Jog, Neelakshi R.; Wagner, Catriona A.; Aberle, Teresa; Chakravarty, Eliza F.; Arriens, Cristina; Guthridge, Joel M.; James, Judith A. (Frontiers in Immunology, 2024)
Neutrophil dysregulation, particularly of a low-density subset, is associated with systemic lupus erythematosus (SLE); however, the exact role of normal-density neutrophils in SLE remains unknown. This study compares activation and functional phenotypes of neutrophils from SLE patients and healthy controls to determine potential contributions to SLE pathogenesis. Surface activation markers and release of neutrophil extracellular traps (NETs), granule proteins, and cytokines/chemokines were measured in resting and stimulated neutrophils from SLE patients (n=19) and healthy controls (n=10). Select miRNA and mRNA involved in neutrophil development and function were also measured. Resting SLE neutrophils exhibited fewer activation markers compared to control neutrophils, and activation markers were associated with different plasma cytokines/chemokines in SLE patients compared to healthy controls. However, activation markers increased similarly in SLE and control neutrophils following stimulation with a TLR7/8 agonist, neutrophil growth factors, and bacterial mimic. At the resting state, SLE neutrophils produced significantly more CXCL10 (IP-10), with trends toward other increased cytokines/chemokines. Following stimulation, SLE neutrophils produced fewer NETs and proinflammatory cytokines compared to control neutrophils but more MMP-8. In addition, SLE neutrophils expressed less miR130a, miR132, miR27a, and miR223. In conclusion, SLE neutrophils exhibit distinct functional responses compared to control neutrophils. These functional differences may result from differential gene expression via miRNAs. Furthermore, the differences in functional phenotype of SLE neutrophils suggest that they may contribute to SLE differently dependent on the inflammatory milieu.